1989
DOI: 10.1136/hrt.61.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of colour flow imaging in the diagnosis of left ventricular pseudoaneurysm.

Abstract: We studied 11 cases of left ventricular pseudoaneurysm (nine patients) diagnosed by colour flow imaging and we describe the diagnostic features of cross sectional imaging and Doppler echocardiography and the advantages ofthe colour flow imaging technique over both other ultrasound techniques and left ventricular angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
4

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 12 publications
(1 reference statement)
0
19
0
4
Order By: Relevance
“…They most commonly present with heart failure symptoms, chest pain and dyspnoea, but they are asymptomatic in 10% of the cases. Currently, echocardiography (transthoracic or transesophageal) is the diagnostic standard [4] for diagnosis of pseudoaneurysms as it has the ability to visualize the heart in different planes and distinguish the myocardium from other structures. Characteristic echocardiographic findings suggestive of a false aneurysm include a sharp discontinuity of endocardial image at the site of pseudoaneurysm communication with the left ventricular cavity, a saccular or globular contour of the false aneurysmal chamber and the presence of a relatively narrow orifice compared with the diameter of the aneurysm fundus [5] .…”
Section: Discussionmentioning
confidence: 99%
“…They most commonly present with heart failure symptoms, chest pain and dyspnoea, but they are asymptomatic in 10% of the cases. Currently, echocardiography (transthoracic or transesophageal) is the diagnostic standard [4] for diagnosis of pseudoaneurysms as it has the ability to visualize the heart in different planes and distinguish the myocardium from other structures. Characteristic echocardiographic findings suggestive of a false aneurysm include a sharp discontinuity of endocardial image at the site of pseudoaneurysm communication with the left ventricular cavity, a saccular or globular contour of the false aneurysmal chamber and the presence of a relatively narrow orifice compared with the diameter of the aneurysm fundus [5] .…”
Section: Discussionmentioning
confidence: 99%
“…Roelandt et al described the presence of bidirectional color flow Doppler between an extracardiac echo-free space and the left ventricle that allowed distinction between a simple pericardial effusion and a LVPSA [17]. Sutherland et al reported a series of cases in which color Doppler imaging was superior to both pulsed and continuous wave Doppler in detecting flow into a LVPSA [18]. It seems likely that the turbulence and size of a jet in the presence of a pseudoaneurysm would be quite different from the flow seen with a true aneurysm, but this distinction has not been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Alguns pseudoaneurismas inferiores podem passar desapercebidos ao ecocardiograma transtorácico. Nestes casos, a ventriculografia isotópica é um método melhor para o diagnóstico 3,15 . A presença de uma cavidade extracardíaca sugere um pseudoaneurisma 3 .…”
Section: Discussionunclassified